2018
DOI: 10.5713/ajas.17.0298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of polymorphisms in MITF and DCT genes and their associations with plumage colors in Asian duck breeds

Abstract: ObjectiveThe aim of this study was to investigate the effect of single nucleotide polymorphisms (SNPs) of the melanogenesis associated transcription factor (MITF) and dopachrome tautomerase (DCT) genes on plumage coloration in Asian native duck breeds. MITF encodes a protein for microphthalmia-associated transcription factor, which regulates the development and function of melanocytes for pigmentation of skin, hair, and eyes. Among the tyrosinase-related family genes, DCT is a pigment cell-specific gene that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…The specific association of SNP involved in the melanogenesis pathway and plumage color in different breeds of common ducks has been reported (Rahayu et al, 2015;Sultana et al, 2018). However, to the best of our knowledge, the present study is the first to demonstrate that the intergeneric maternal SNP of MC1R gene are associated with the plumage color of their offspring.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…The specific association of SNP involved in the melanogenesis pathway and plumage color in different breeds of common ducks has been reported (Rahayu et al, 2015;Sultana et al, 2018). However, to the best of our knowledge, the present study is the first to demonstrate that the intergeneric maternal SNP of MC1R gene are associated with the plumage color of their offspring.…”
Section: Discussionmentioning
confidence: 51%
“…Over the past decade, traditional selection of maternal lines of mule duck, including Tsaiya and Pekin ducks, have successfully improved mule ducks whose white plumage is generally accepted by consumers in Taiwan. Many studies have demonstrated the polymorphisms of genes involved in the melanogenesis pathway associated with plumage coloration between avian species (Hoque et al, 2013;Zhang et al, 2015;Ran et al, 2016;Sultana et al, 2017;Sultana et al, 2018). However, little is known about the relationship between gene polymorphism and plumage coloration in intergeneric hybrids.…”
Section: Yi-chen Tumentioning
confidence: 99%
See 2 more Smart Citations
“…Melanogenesis is regulated by a series of transcription factors, among which microphthalmia-associated transcription factor (MITF) plays an important role (Chen et al, 2018b;Ishii et al, 2017). MITF promotes melanogenesis by inducing melanogenesis-related genes, such as TYR, TYRP1, TYRP2, and RAB27A (Alves et al, 2017;Sultana et al, 2018). Studies have shown that the phosphorylation state of the transcription factor CRE-binding protein (CREB) promotes the expression of MITF by binding to and activating the promoter of MITF, thereby promoting the activation of MC function (Alam et al, 2018;Shin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%